2020
DOI: 10.3390/cells9051219
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Endoplasmic Reticulum in NLRP3 Inflammasome Activation

Abstract: The NLRP3 (nucleotide-binding domain, leucine-rich-repeat-containing family, pyrin domain-containing 3) inflammasome senses pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs), and activates caspase-1, which provokes release of proinflammatory cytokines such as interleukin-1β (IL-1β) and IL-18 as well as pyroptosis to engage in innate immune defense. The endoplasmic reticulum (ER) is a large and dynamic endomembrane compartment, critical to cellular function of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 183 publications
(263 reference statements)
0
55
0
Order By: Relevance
“…Pharmacological relief of hypothalamic ER stress can reverse these metabolic alterations (130). Similarly, Brenda et al found that, following palmitic acid treatment, ER stress was induced only after MFN2 downregulation (30). These results indicate that ER stress may be the key pathway through which impaired MAM integrity leads to defects in hypothalamic insulin signaling.…”
Section: Altered Mam Integrity In Brain Insulin Resistancementioning
confidence: 92%
See 2 more Smart Citations
“…Pharmacological relief of hypothalamic ER stress can reverse these metabolic alterations (130). Similarly, Brenda et al found that, following palmitic acid treatment, ER stress was induced only after MFN2 downregulation (30). These results indicate that ER stress may be the key pathway through which impaired MAM integrity leads to defects in hypothalamic insulin signaling.…”
Section: Altered Mam Integrity In Brain Insulin Resistancementioning
confidence: 92%
“…MAMs are now known to be specialized lipid raft-like regions. These lipid microdomains are a dynamic assemblage of sphingolipids and cholesterol that can move within the fluid lipid bilayer and function as platforms for the attachment of proteins during signal transduction (30). These proteins can be enzymes, transporters, kinases, ion channels, or phosphatases (9), indicating that MAMs participate in various cellular processes, such as calcium homeostasis, lipid metabolism, mitochondrial physiology, ER stress, and inflammation.…”
Section: The Mam-mediated Regulation Of Cellular Homeostasis and Its mentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin can therefore influence TXNIP function, especially the MERCs-related one, which is important for inflammatory response. Indeed, TXNIP accumulates at MERCs in response to oxidative stress and mediates production of interleukin (IL)-1β [129,133,134].…”
Section: Mercs Modulator Class Iii: Targeting Mercs Through Modulatiomentioning
confidence: 99%
“…Moreover, after activation of NLRP3 inflammasomes, advanced cytokine loops (IL-1β, IL-18) are subsequently formed, which can then stimulate the generation of proinflammatory cascades and eventually establish a vicious cycle between inflammation and mitochondrial dysfunction. NFκB-regulated NLRP3 inflammasomes activation involves the following critical organelles significant to cellular function: mitochondria, ER membranes, and MAMs [ 39 ].…”
Section: Nfκb-driven Inflammation and Mitochondrial Dysfunction Inmentioning
confidence: 99%